The Reception Of Islamic Religious Activists (Rohis) On Religious Reading Materials In Sman 48 East Jakarta And Sma Labschool East Jakarta - Mahmudah Nur (Analisa: Journal of Social Science and Religion, 2015)
This paper is motivated by some studies that suggest that the majority of students in Jakarta have a narrow and exclusive religious understanding, and tend to agree in a violent action to resolve the problem of religion and morals. This research is a descriptive research that more emphasis on qualitative data analysis and using reception approach. Reception analysis is used in order to describe a religious reading material within religious extra-organization activists, and describes the reception of student activists on the reading material that focuses on interpretation and the motivation of students in selection of reading materials. This research suggests that ROHIS activist in SMAN 48 East Jakarta And SMA Labschool East Jakarta prefers to read some books that the genre were Islamic novels and the books about women, which had simple language, easily understanding, and communicative. Student motivation in choosing reading material is more to support their worship activities, either obligatory or sunnah, that relate to their daily activities.